Multiproduct Cournot oligopoly - Myatt, D; Johnson, J (University of Oxford, 2005)
We present a general Cournot model in which each firm may sell multiple quality-differentiated products. We use an upgrades approach, working not with the actual products, but instead with upgrades from one quality to the next. The properties of single-product Cournot models carry over to the supply of upgrades, but not necessarily to the supply of complete products. A firm's product line is determined by the properties of demand, its costs, and competitor characteristics. For symmetric firms, these determinants reduce to returns to quality and changes in demand elasticity as quality increases. For asymmetric firms whose (potentially endogenous) technological capabilities are defined by their maximum feasible qualities, gaps in product lines are determined precisely by the capabilities of lesser rivals. Strategic commitment to product lines prior to quantity competition is considered. Incentives to so commit are markedly different from those under price-setting models.